2011
DOI: 10.1002/lt.22220
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress is a mediator of posttransplant injury in severely steatotic liver allografts

Abstract: Hepatic steatosis continues to present a major challenge in liver transplantation. These organs have been shown to have increased susceptibility to cold ischemia/reperfusion (CIR) injury in comparison with otherwise comparable lean livers; the mechanisms governing this increased susceptibility to CIR injury are not fully understood. Endoplasmic reticulum (ER) stress is an important link between hepatic steatosis, insulin resistance, and metabolic syndrome. In this study, we investigated ER stress signaling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 45 publications
6
44
0
1
Order By: Relevance
“…C/EBP homologous protein (CHOP) plays a key role in ER stress-induced cellular damage and its genetic deletion attenuated myocardial and brain IRI in vivo (26, 35), as well as hepatocyte death in vitro (36). Alleviation of ER stress by chemical chaperons, therefore, effectively protected organs from IRI (14, 25, 27, 28). Although several studies, including our own, have demonstrated a potential role of ER stress in regulating inflammatory immune response against IR (13, 28, 35), the underlying mechanism was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBP homologous protein (CHOP) plays a key role in ER stress-induced cellular damage and its genetic deletion attenuated myocardial and brain IRI in vivo (26, 35), as well as hepatocyte death in vitro (36). Alleviation of ER stress by chemical chaperons, therefore, effectively protected organs from IRI (14, 25, 27, 28). Although several studies, including our own, have demonstrated a potential role of ER stress in regulating inflammatory immune response against IR (13, 28, 35), the underlying mechanism was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, LPS stimulation in the lungs increased markers of ER stress, inflammatory cytokines and NFKB and HIF1A activity, which were then reduced following 4-PBA treatment [76]. TUDCA also suppressed activation of NFKB and proinflammatory cytokines when administered to treat allograft injury caused associated with liver transplantation [77]. NFKB is an important upstream regulator of proinflammatory cytokines, PTGS2, PGs, and MMP9 [78].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated the importance of CHOP in cold ischemia and reperfusion injury of the liver [5], and we have demonstrated autophagy as a mediator of ER stressinduced cell death in hepatocytes [6]. The main function of autophagy is to clear unwanted components in the cytoplasm, and it is believed to be beneficial to cell survival.…”
Section: Introductionmentioning
confidence: 94%